Multidimensi dari Teologi Terhadap Teologi Manajemen - Aan Mirkan; Agum Pinanda; Ditha Olivia; Andri Nata Nael; Novi Arianti; Sarmauli Sarmauli (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2025)
This study aims to analyze the multidimensional integration between theology and management in developing an ethical, holistic, and human-centered paradigm of Christian leadership. The research employs a qualitative descriptive method through a comprehensive literature analysis of contemporary theological and managerial works. The findings demonstrate that theology serves as a normative foundation that shapes managerial decision-making processes and guides the moral direction of organizations. The integration of spiritual, social, and practical dimensions produces a leadership model emphasizing love, honesty, justice, responsibility, and service. These results indicate that theology functions not merely as a reflection of faith but also as a conceptual framework that directs management practices toward sustainability and social balance. The multidimensional theological approach bridges faith values with concrete actions in modern organizations, offering substantial contributions to the development of character-based, humanistic, and transformative management. Consequently, this study enriches the academic discourse on theology-management integration and provides a conceptual reference for constructing ethical leadership models in the global era.